I Don't Want to Think About It!: A Qualitative Study of Hypertensive Women's Awareness and Perception of Heart Disease - Sutantri; Nina Dwi Lestari; Resti Yulianti Sutrisno; Laili Indah Wulandari; Riska Putri Rachmawati (Universitas Airlangga, 2023)
Background: Research has shown an increasing number of young women between the ages 35 and 54 having heart attacks. However, data demonstrated a persisting failure to raise women's awareness of cardiovascular disease risk. Moreover, very little has been done to date in low- and middle-income countries to educate women on cardiovascular disease risks and the high mortality rates for women. Aims: The aim of this study was to explore hypertensive women's awareness and perceptions of heart disease. Methods: A qualitative research design using semi-structured interviews was performed. Data were analyzed using an inductive thematic analysis approach. Results: In total, 25 women participated in this study. Three main themes emerged: (1) perception of heart disease and its risk factors, (2) ‘I don't want to think about it': perspectives on future risk, and (3) strategies to prevent heart disease. From the participants' narratives, it was evident that the women in this study had limited knowledge related to heart disease. Although all participants suffered from hypertension, the women still underestimated their risk of developing heart disease in the future. Many women believed that praying to God and maintaining an optimistic mindset could protect them from heart disease. Conclusion: The study's findings highlight a clear indication of the need to implement renewed strategies for educating women about cardiovascular health tailored to target the rural populations in Indonesia. Raising women's awareness might reduce their risk of suffering from cardiovascular disease in the future.